Efektivitas Daun Sirsak (Annona muricata) dalam Mematikan Larva Nyamuk Aedes aegypti - Fajar Akbar; Willyam Rivaldy; Haeranah Ahmad; Askur Askur; Muhammad Rusdi (FORIKES, 2023)
To control the Aedes aegypti mosquito as a vector of dengue hemorrhagic fever so far, most of it still uses chemicals, so it is necessary to use materials that do not have the potential to damage the environment. This study aimed to determine the effectiveness of soursop leaf extract to kill Aedes aegypti mosquito larvae. This research was an experimental study that examined the effectiveness of soursop leaves as a natural larvicidal for Aedes aegypti larvae. The test was carried out 3 times, each with a concentration of 5%, 15%, 25%, so that 25 Aedes aegypti larvae were needed as samples for each concentration. Observations were made every 6 hours for 24 hours. Observations were analyzed by comparing the number of dead larvae for each concentration. At all concentrations, it was found that all larvae died (100%) at the third observation (18 hours). The higher the concentration and duration of administration of soursop leaf extract to Aedes aegypti larvae, the higher the potential for larval death. It was concluded that soursop leaf extract was effective as a natural larvicide for Aedes aegypti larvae.Keywords: Aedes aegypti; soursop leaf; larvicides ABSTRAK Pengendalian nyamuk Aedes aegypti sebagai vektor penyakit demam berdarah dengue selama ini, kebanyakan masih menggunakan bahan kimia, maka itu diperlukan bahan yang tidak berpotensi merusak lingkungan. Penelitian ini bertujuan untuk mengetahui efektivitas ekstrak daun sirsak untuk membunuh larva nyamuk Aedes aegypti. Penelitian ini merupakan studi eksperimental yang menguji efektivitas daun sirsak sebagai larvasida alami bagi larva Aedes aegypti. Pengujian dilakukan 3 kali, masing-masing dengan konsentrasi 5%, 15%, 25%, sehingga dibutuhkan 25 larva Aedes aegypti sebagai sampel untuk setiap konsentrasi. Pengamatan dilakukan setiap 6 jam selama 24 jam. Hasil pengamatan dianalisis dengan cara membandingkan jumlah larva yang mati untuk setiap konsentrasi. Pada semua konsentrasi, ditemukan bahwa seluruh larva mati (100%) pada pengamatan ketiga (18 jam). Semakin tinggi konsentrasi dan durasi pemberian ekstrak daun sirsak pada larva Aedes aegypti, maka semakin tinggi pula potensi kematian larva. Disimpulkan bahwa ekstrak daun sirsak efektif sebagai larvasida alami bagi larva Aedes aegypti.Kata kunci: Aedes aegypti; daun sirsak; larvasida